Mortality impact of viral and microzooplankton upon bacteria and phytoplankton in a eutrophic reservoir in central highlands - Tinh, Tran Thi; Hai, Doan Nhu; Dung, Le Ba (Academia Journal of Biology, 2015)
There were many studies on impact of viral lysis and microzooplankton grazing on the aquatic food web. However, there was a lack of studies that assess the relative importance of both mortality factors in the same time. In this study, we applied the dilution technique to estimate the impact withal of both viral lysis and microzooplankton grazing on bacteria, microalgae, and especially filamentous cyanobacteria in Xuan Huong reservoir, the shallow eutrophic reservoir in Da Lat city. We performed two dilution experiments, the first one was performed in the dry season (January 2014) and another was done in the rainy season (July 2014). We determined viral and bacterial abundances by using epifluorescence microscopy. The abundance of phytoplankton was determined by using light microscope. The study illustrates that viral lysis was the main morality source in the dry season experiment, removing about 65% and 87% of the potential falamentous cyanobacterial and bacterial productions, respectively. Contrarily, microzooplankton grazing removed about 20%; 65% and 80% of the potential algal, unicellular cyanobacteria and bacterial productions, respectively, in the rainy season.